Age and Gender Moderate the Impact of Early Palliative Care in Metastatic Non-Small Cell Lung Cancer. (30th November 2015) - Nipp, Ryan D.; Greer, Joseph A.; El-Jawahri, Areej; Traeger, Lara; Gallagher, Emily R.; Park, Elyse R.; Jackson, Vicki A.; Pirl, William F.; Temel, Jennifer S.
Abstract: Background: Studies demonstrate that early palliative care (EPC) improves advanced cancer patients' quality of life (QOL) and mood. However, it remains unclear whether the role of palliative care differs based upon patients' demographic characteristics. We explored whether age and gender moderate the improvements in QOL and mood seen with EPC. Methods: We performed a secondary analysis of data from a randomized controlled trial of patients with metastatic non-small cell lung cancer. Patients received either EPC integrated with oncology care or oncology care alone. We assessed the degree to which QOL (Trial Outcome Index [TOI]) and mood (Hospital Anxiety and Depression Scale [HADS] and Patient Health Questionnaire 9 [PHQ-9]) outcomes at week 12 varied by patient age (<65) and gender. The week 12 data of 107 patients are included in this analysis. Results: At 12 weeks, younger patients receiving EPC reported better QOL (TOI mean = 62.04 vs. 49.43, p = .001) and lower rates of depression (HADS–Depression = 4.0% vs. 52.4%, p < .001; PHQ-9 = 0.0% vs. 28.6%, p = .006) than younger patients receiving oncology care alone. Males receiving EPC reported better QOL (TOI mean = 58.81 vs. 48.30, p = .001) and lower rates of depression (HADS–Depression = 18.5% vs. 60.9%, p = .002; PHQ-9 = 3.8% vs. 34.8%, p = .008) than males receiving oncology care alone. At 12 weeks, QOL and mood did not differ between study groups for females and older patients. Conclusion: Males and younger patients who received EPC had better QOL and mood than those who received oncology care alone. However, these outcomes did not differ significantly between treatment groups for females or older patients. Abstract : This study analyzed data from a randomized controlled trial of patients with metastatic non-small cell lung cancer who received either early palliative care (EPC) integrated with oncology care or oncology care alone. Males and younger patients who received EPC had better quality of life and mood than those who received oncology care alone. However, these outcomes did not differ significantly between treatment groups for females or older patients.